1
$\begingroup$

Why is this wrong? $$(-1)^3=(-1)^{6/2}=((-1)^6)^{1/2}=1^{1/2}=1$$ It seems logical but I know it's wrong.

$\endgroup$
  • 1
    $\begingroup$ When are you allowed to use which exponentiation laws? Be completely exact: for all laws with $a^b$ et cetera, $a$ is always positive. Right? The reason for this you see in your question. $\endgroup$ – Moritz Mar 4 '15 at 20:10
5
$\begingroup$

Hint: $1$ has more than one possible square root, and you need to check them all when you do a calculation like you are doing.

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ Could you please explain this a little more? $\endgroup$ – Enthusiastic Engineer Mar 4 '15 at 20:21
2
$\begingroup$

The problem is that $$(-1)^3\neq((-1)^6)^{1/2}$$

The well-known identity $$a^{mn}=(a^m)^n$$ stands when $a>0$. It also stands when $m,n\in\Bbb Z$ (provided that $a\neq 0$), but it is false if $a<0$ and the exponents are not integer.

| cite | improve this answer | |
$\endgroup$
-4
$\begingroup$

Hint:

$$\sqrt{9}=3 \land -3$$

People tend to forget these simple things...

| cite | improve this answer | |
$\endgroup$
  • 1
    $\begingroup$ People also forget that $\sqrt{9}=3 \land -3$ means $\sqrt{9}$ equals $3$ and $-3$ simultaneously. Technically it should be $\sqrt{9}=3 \vee -3$, or more correctly, $\sqrt{9} = \pm 3$. $\endgroup$ – graydad Mar 4 '15 at 20:41

Not the answer you're looking for? Browse other questions tagged or ask your own question.